The effects of a secondary school scholarship on youth outcomes: Evidence from a randomized trial - Leight, Jessica (International Food Policy Research Institute, 2025)
Although primary school enrollment has steadily increased in sub-Saharan Africa in recent years, enrollment in secondary school remains generally low in comparison with other regions (Evans and Mendez Acosta 2021). In Ethiopia, enrollment in lower secondary school roughly doubled over the past decade to reach an estimated 46 percent in 2021–2022, but substantial heterogeneity exists across rural and urban areas and across poorer and richer households (Tiruneh and Molla 2024). In rural areas, long distances from home to school often pose a substantial barrier to secondary school enrollment, especially for poor households. In addition to the real or perceived risks of insecurity linked to attendance – encountering insecure conditions along the route, or risks for youth who reside away from home to attend – these lengthy distances imply substantial out-of-pocket costs for transportation or accommodation, and households may struggle to manage these costs (Leight et al. 2022). Limited post-primary educational attainment can have substantial adverse effects for youth, limiting their opportunities for future employment and income generation and increasing the likelihood of early marriage for girls (Giacobino et al. 2024).